Oral Colonization by Nosocomial Pathogens During Hospitalization in Intensive Care Unit and Prevention Strategies - Kazemian, Hossein; Bourbour, Samane; Beheshti, Maryam; Bahador, Abbas (Recent Patents on Anti-Infective Drug Discovery, 2017)
Background: Critically ill patients are very susceptible to a variety of disorders and infections during hospitalization in Intensive Care Units [ICU]. Among these problems, nosocomial infections are major causes of morbidity and mortality. Methods: Nosocomial pneumonias, specifically ventilator associated pneumonias have become a major health care issue. The implication of oral care in hospital presents challenges that can prevent or reduce the risk of nosocomial pneumonias in ICU. In this review article, we reviewed the most important nosocomial pathogens which colonize the oral cavity and causes severe infections during hospitalization in ICU. Conclusion: Finally, we discuss that the prevention strategies against oral colonization of nosocomial pathogens include classical methods and novel methods such as Photodynamic therapy, NO based therapy, anti-virulence therapy and other new under investigation antimicrobial strategies.
Keywords: ICU